Inhibition of Insulin Amyloid Fibrillation by a Novel Amphipathic Heptapeptide: MECHANISTIC DETAILS STUDIED BY SPECTROSCOPY IN COMBINATION WITH MICROSCOPY - Ratha, Bhisma N. (J Biol Chem, 2016)
The aggregation of insulin into amyloid fibers has been a limiting factor in the development of fast acting insulin analogues, creating a demand for excipients that limit aggregation. Despite the potential demand, inhibitors specifically targeting insulin have been few in number. Here we report a non-toxic and serum stable-designed heptapeptide, KR7 (KPWWPRR-NH(2)), that differs significantly from the primarily hydrophobic sequences that have been previously used to interfere with insulin amyloid fibrillation. Thioflavin T fluorescence assays, circular dichroism spectroscopy, and one-dimensional proton NMR experiments suggest KR7 primarily targets the fiber elongation step with little effect on the early oligomerization steps in the lag time period. From confocal fluorescence and atomic force microscopy experiments, the net result appears to be the arrest of aggregation in an early, non-fibrillar aggregation stage. This mechanism is noticeably different from previous peptide-based inhibitors, which have primarily shifted the lag time with little effect on later stages of aggregation. As insulin is an important model system for understanding protein aggregation, the new peptide may be an important tool for understanding peptide-based inhibition of amyloid formation.